1981
DOI: 10.1136/bmj.282.6260.258
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of autoimmune thyroiditis.

Abstract: Buckton KE, O'Riordan ML, Ratcliffe SG, et al. A G-banded study of chromosomes in liveborn infants. Ann Hum Genet 1980;43 :227-39. 5 Gosden CM, Wright MO, Paterson WG, Grant KA. Clinical details, cytogenetic studies and cellular physiology of a 69,XXX fetus with comments on the biological effect of triploidy in man. J Med Genet 1976; 13:371-80. 6 Gosden CM, Brock DJH. Morphology of rapidly adhering amniotic fluid cells as an aid to the diagnosis of neural tube defects. Lancet 1977;i: 919-22. 7 Gosden CM, Brock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3
4

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(87 citation statements)
references
References 20 publications
6
74
3
4
Order By: Relevance
“…1,2 However, in the present study, among all patients who underwent FNA of the thyroid over an eight year period in Kuwait, the highest prevalence of HT was found in women between the ages of 16 and 35. This shows that HT is more often encountered in the younger age group in Kuwait.…”
Section: Discussionmentioning
confidence: 64%
“…1,2 However, in the present study, among all patients who underwent FNA of the thyroid over an eight year period in Kuwait, the highest prevalence of HT was found in women between the ages of 16 and 35. This shows that HT is more often encountered in the younger age group in Kuwait.…”
Section: Discussionmentioning
confidence: 64%
“…The causes of SCH resemble the causes of HYPO, where autoimmune thyroiditis is the most frequent cause (9). Table 1 lists studies of the natural history of SCH (10)(11)(12)(13)(14)(15)(16)(17)(18). Progression of SCH to HYPO is in the order of 5-8%/year.…”
Section: Introductionmentioning
confidence: 99%
“…Progression of SCH to HYPO is in the order of 5-8%/year. Normalisation of thyroid function is another possible outcome, and many patients have stable SCH and do not experience systematic deterioration in thyroid function for years (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In longitudinal studies of thyroid autoimmunity 19,20 Effects of L-thyroxine therapy on goiter size, serum TSH, and antithyroid antibody levels in HD Since early studies in the 1950s (Table 1), a generation or longer elapsed before additional research confirmed that thyroxine treatment was associated with reduced thyroid size 21,22 and decreased antithyroid antibody levels 21 in either adult 21 or juvenile 22 patients with HD. A longitudinal study of goitrous HD and idiopathic myxedema 23 also found that L-thyroxine therapy for 2 to 4 years reduced goiter size (p < 0.050) as well as antibody levels (p < 0.001) in HD, in both hypothyroid HD and idiopathic myxedema, but not in patients with euthyroid HD.…”
Section: Hypothesis Raised: Could Thyroxine Treatment Diminish Risk Omentioning
confidence: 99%